Pengaruh latihan fonasi vokal “a” berdasarkan lee silverman voice treatment loud terhadap kejelasan bicara pasien stroke iskemik - Rahayu, Sisri; Sujianto, Untung; Husna, Elfira; Ashra, Fauzi; Putra, Yuhendri; Liza, Fera (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Speech nerve disorders due to stroke cause slurred speech. Lee Silverman Loud Voice Therapy can be applied using the Swanson technique to help stimulate the speech muscles. Purpose: To determine the effect of